Conservation of neural progenitor identity and the emergence of neocortical neuronal diversity. (October 2021) - Shohayeb, Belal; Muzar, Zukhrofi; Cooper, Helen M.
Abstract: One paramount challenge for neuroscientists over the past century has been to identify the embryonic origins of the enormous diversity of cortical neurons found in the adult human neocortex and to unravel the developmental processes governing their emergence. In all mammals, including humans, the radial glia lining the ventricles of the embryonic telencephalon, more recently reclassified as apical radial glia (aRGs), have been identified as the neural progenitors giving rise to all excitatory neurons and inhibitory interneurons of the six-layered cortex. In this review, we explore the fundamental molecular and cellular mechanisms that regulate aRG function and the generation of neuronal diversity in the dorsal telencephalon. We survey the key structural features essential for the retention of the highly polarized aRG morphology and therefore impose aRG identity after cytokinesis. We discuss how these structures and associated molecular signaling complexes influence aRG proliferative capacity and the decision to undergo proliferative self-renewing symmetric or neurogenic asymmetric divisions. We also explore the intriguing and complex question of how the extensive neuronal diversity within the adult neocortex arises from the small aRG population located within the cortical proliferative zone. We further highlight the recent clonal lineage tracing and single-cell transcriptomic profiling studies providing compelling evidence that individual neuronal identity emerges as a consequence of exposure to temporally regulated extrinsic cues which coordinate waves of transcriptional activity that evolve over time to drive neuronal commitment and maturation. Highlights: Apical radial glia (aRGs) produce all neurons of the neocortex. aRG morphology influences self-renewal versus neuronal differentiation. Neuronal lineage commitment is partially pre-programmed in multipotent aRGs. aRGs switch their neuronal output in a temporally restricted manner. Transcriptional waves emerge post-cell cycle exit to specify neuronal identity.